Postoperative Delirium in Adult Patients Undergoing Surgery: A Prospective Observational Study in a Peripheral Hospital in the Southern Region of India - Basavaraj Karan; Parli Raghavan Ravi (Journal of Marine Medical Society)
Introduction: Delirium is one of the most deleterious complications in the postoperative period. The incidence of it in the Indian rural population undergoing surgery is not well studied. Materials and Methods: Eight hundred and fifteen patients coming for surgery in a peripheral Indian hospital in the southern part of the country were taken up for an observational study. All patients who had a Mini-Mental State Examination (MMSE) score of above 25 were taken into the study, postoperatively confusion assessment method was used to assess the delirium. Patients were followed up for 7 days. Various modifiable and nonmodifiable risk factors were studied using SPSS (version 26.0) for statistical analysis. Results: Six out of 815 (0.73%) patients had postoperative delirium (POD). The average age of the population was 43 ± 12.61. All six patients were above the age of 60 years. POD was found statistically significant with higher grades of the American Society of Anaesthesiologists, long duration of surgery and anesthesia, more fluid transfusion and blood loss, and sevoflurane in comparison to desflurane. Conclusion: Preoperative screening with MMSE and reducing the modifiable risk factors can be used to strategize providing anesthesia care for the surgical population. The risk factors are almost the same in the rural population in comparison to the known risk factors for the development of POD.